2019
DOI: 10.31989/ffhd.v9i11.665
|View full text |Cite
|
Sign up to set email alerts
|

Effects of six weeks consumption of coconut milk oil on vascular functions and fasting blood glucose and lipid profile in middle-aged male rats

Abstract: Background: Coconut milk consumption in middle-aged male rats can cause increased blood vessel endothelial nitric oxide synthase (eNOS) and cystathionine-γ-lyase (CSE) protein expression, and decreased fasting blood glucose.Objective: The present study aimed to investigate whether coconut milk oil (CO), the major constituents of the coconut milk, was responsible for those effects.Methods: CO was isolated from dried fresh coconut milk and gavaged (1 and 3 ml/kg) to middle-aged male rats for 6 weeks. Blood bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This leads to increased production of NO and H2S from blood vessels, resulting in reduced vasocontraction to phenylephrine and improved relaxation to acetylcholine. These findings suggest positive effects on cardiovascular markers [39][40][41] . It is important to note that these processes take place when the fat intake is wholesome (i.e., not refined into specific components) and under appropriate circumstances (i.e.…”
Section: Fatmentioning
confidence: 59%
“…This leads to increased production of NO and H2S from blood vessels, resulting in reduced vasocontraction to phenylephrine and improved relaxation to acetylcholine. These findings suggest positive effects on cardiovascular markers [39][40][41] . It is important to note that these processes take place when the fat intake is wholesome (i.e., not refined into specific components) and under appropriate circumstances (i.e.…”
Section: Fatmentioning
confidence: 59%
“…Meanwhile our research group studied middle-aged male rats and found that the consumption of pure dried fresh coconut milk caused up-regulation of blood vessel endothelial nitric oxide synthase (eNOS) and cystathionine γ-lyase (CSE) protein expression, which resulted in an attenuation of the contractile response to phenylephrine and potentiate relaxation to acetylcholine on the rats' thoracic aortic rings, with a decreased fasting plasma glucose level (Jansakul et al, 2018). Further, these effects were very similar to those resulting from the consumption of dried fresh coconut milk oil except that the retroperitoneal fat accumulation was increased (Naphatthalung et al, 2019), which indicates that there must be other active components in the coconut milk that counteract fat accumulation from the coconut milk oil.…”
Section: Introductionmentioning
confidence: 93%